DESIGN AND PREPARATION OF THE ACCOUNTING RECORDING SYSTEM OF REZEKINDO MAKMUR SENTOSA STORE - Meily Juliani; Angelline Tu (ConCEPt - Conference on Community Engagement Project, 2023)
Rezekindo Makmur Sentosa store is one of the Micro, Small and Medium Enterprises (MSMEs) in Batam City, engaged on fruit market sector. This business is located at Komplek Nagoya Newton Blok E No. 1-2, Jodoh. Rezekindo Makmur Sentosa is a fruit shop for both imported and local fruits. Rezekindo Makmur Sentosa store still uses a simple accounting recording system, namely manual recording of all sales, purchases and stock inventory transactions. Every transaction that occurs is only recorded manually, so that transactions are not systematically arranged and cannot produce financial reports that can provide clear information to business owners. the method used in collecting data is by observing and interviewing. This activity resulted in accounting records designed by student in the form of a Microsoft Access program so entrepreneurs can easily make records and the system can automatically generate the financial reports. This system can also improve business flow to more efficient and effective business operations.